Effects of Isosorbide Mononitrate and/or Cilostazol on Hematological Markers, Platelet Function, and Hemodynamics in Patients With Lacunar Ischaemic Stroke: Safety Data From the Lacunar Intervention-1 (LACI-1) Trial - Appleton, Jason P.; Blair, Gordon W.; Flaherty, Katie; Law, Zhe Kang; May, Jane; Woodhouse, Lisa J.; Doubal, Fergus; Sprigg, Nikola; Bath, Philip M.; Wardlaw, Joanna M. (Frontiers in Neurology, 2019)
Background Cilostazol and isosorbide mononitrate (ISMN) are candidate treatments for cerebral small vessel disease and lacunar ischaemic stroke. As both drugs may influence haemoglobin and platelet count, and haemodynamics, we sought to assess their effects in the lacunar intervention-1 (LACI-1) trial. Methods 57 lacunar ischaemic stroke patients were randomised to immediate ISMN, cilostazol, or their combination for 9 weeks in addition to guideline stroke prevention. A fourth group received both drugs with a delayed start. Full blood count, platelet function, peripheral blood pressure (BP), heart rate and central haemodynamics (Augmentation index, Buckberg index) were measured at baseline, and weeks 3 and 8. Differences were assessed by multiple linear regression adjusted for baseline and key prognostic variables. Registration ISRCTN 12580546. Results At week 8, platelet count was higher with cilostazol vs. no cilostazol (mean difference, MD 35.73, 95% confidence intervals, 95% CI 2.81-68.66, p=0.033), but no significant differences were noted for haemoglobin levels or platelet function. At week 8, BP did not differ between the treatment groups, whilst heart rate was higher in those taking cilostazol vs. no cilostazol (MD 6.42, 95% CI 1.17-11.68, p=0.017). Buckberg index (subendocardial perfusion) was lower in those randomised to cilostazol vs. no cilostazol and in those randomised to both drugs vs. either drug. Whilst ISMN significantly increased unadjusted augmentation index (arterial stiffness, MD 21.19, 95% CI 9.08-33.31, p=0.001), in isolation both drugs non-significantly reduced augmentation index adjusted for heart rate. Conclusions Cilostazol increased heart rate and platelet count, and reduced Buckberg index, whilst both drugs may individually reduce arterial stiffness adjusted for heart rate. Neither drug had clinically significant effects on haemoglobin or platelet function over 8 weeks. Further assessment of the safety and efficacy of these medications following lacunar ischaemic stroke is warranted.